Primary prevention activities of the diabetic foot and self-care activities in patients with type 2 diabetes in the Hospital II Clínica Geriátrica San Isidro Labrador, Essalud - Mesares Damiano, Gloria Rosa (2019)
Objetives: To identify which primary prevention of diabetic foot hits the nurse and what self-careactivities performed by the patient with type 2 diabetes. Materials and Methods: The type of studyis descriptive and cross-sectional data collection survey was applied to nurses and diabetic patientsover 18 years. Results: The results show that 83.6% of nurses performed the assessment of thefoot, provides education 90.9%. 72.7% provide foot self-care techniques. Recommended 92.7%quit smoking and 98.2% reported the importance of attending to his control. With regard to self-carepractices performed by the patients, 46.4% have a moderate level of self-care, 69.6% check their feet,42.9% did not check the inside of their shoes, 60% no apply moisturizers, 44.6% continues to add sugarto their drinks, 45.5% of overweight patients, including both sexes. Conclusions: Most of nurses takealmost all activities of primary prevention of diabetic foot highlighting an important activity assessmentof the foot. Furthermore, there is a regular practice of self-performed by the patient, especially in thedaily observation of the foot.